Criterion for assessing the causes of road accidents according to a specific age group of drivers in Poland based on road incidents occurred in 2020 - Podgórska, Agnieszka; Rajchel, Jan; Kępa, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
This research analyses the main causal factors that lead to road accidents. Particular focus has been on the demographics of drivers and in particular on the age group given that younger drivers account for the highest number of road safety-related incident/ accidents and fatalities. Other factors impacting road safety include the adequacy of the national driver training system, legislative requirements and organisational solutions for ensuring road safety. Behavioural and characteristics of drivers are considered as part of the causal analysis.

Niniejsze badanie analizuje główne czynniki sprawcze, które prowadzą do wypadków drogowych. Szczególny nacisk położono na demografię kierowców, a zwłaszcza na grupę wiekową, biorąc pod uwagę, że młodsi kierowcy odpowiadają za największą liczbę incydentów/wypadków i ofiar śmiertelnych związanych z bezpieczeństwem drogowym. Analizie poddano także inne czynniki wpływające na bezpieczeństwo ruchu drogowego, takie jak adekwatność krajowego systemu szkolenia kierowców, wymagania prawne i rozwiązania organizacyjne zapewniające bezpieczeństwo ruchu drogowego. Zachowanie i cechy kierowców są brane pod uwagę jako część analizy przyczynowej.
Keywords: traffic; driver; road incident; causes; effects; safety; ruch; kierowca; zdarzenie drogowe; przyczyny; skutki; bezpieczeństwo